Forensic Law in Hypoglycaemia-2 - Derek C Beatty; Dr. Christina G Yap (Studies in Law and Justice, 2023)
We start 2023 with the sad statistic that a 39% rise in the number of children needing help for serious Mental Health including eating disorders have been statistically analysed from NHS data with 1,169,515 under 18’s referred for mental health treatment in 2021/22 compared to 839,750 in 2020/21 and 850,741 referrals in 2019/20. Can Hypoglycaemia Unawareness offer possible understanding of this sad disclosure to help children, youths, and families?